Engineering Drawing Fundamentals - Parker, M. A. (Maurice Arthur), 1928-; Dennis, L. J. (Stanley Thornes, 1992)
Written to cover the engineering drawing material in the BTEC unit, Engineering Fundamentals, this book aims to present the basic principles of the engineer's language without unnecessary elaboration. Many examples supplement the text, and some of them are laid out in step-by-step form.